Management control systems in complex settings emerging research and opportunities - Zanin, Filippo 1974-; Comuzzi, Eugenio 1963-; Costantini, Antonio 1974- (Advances in logistics, operations, and management science (ALOMS) book series, 2018)
"This book provides an overview about complexity theory, management control systems and value creation, as well as strategic issues in complex firms. It covers specific items of management control, and especially managing economic value and strategic planning in complex firms. It presents a qualitative case study on emerging and innovative research themes about control in complex settings"...